THE ROLE OF FISCAL COMPETITIVENESS IN STRENGTHENING THE COMPETITIVENESS OF BOSNIA AND HERZEGOVINA - Maksimović, Ljiljana; Birčaković, Ružica (International Journal of Economic Practice and Policy, 2013)
A country’s competitiveness is the domain of economic theory, which analyzes the facts and policies that shape the country's ability to create and maintain an environment that creates greater value for companies and prosperity for its citizens  (Garelli, 2009). Competitiveness has become one of the most important issues of our time. Its significance, in addition to the traditional role of striving to be better than others, has been contributed by the global economic crisis. Enhancing productivity and competitiveness must be the basic idea of economic policy. The World Economic Forum has been conducting an analysis of international competitiveness for three decades. Bosnia and Herzegovina gained the 88th place in economic competitiveness ranking in 2012. The tax rates are seen as one of the reasons for such a position. Starting from this, this paper attempts to analyze the tax rates and the tax burden on income tax in Bosnia and Herzegovina  and to perform the comparative analysis with neighboring countries in order to point out the limited range of tax policies to strengthen the country’s competitiveness.
Keywords: analysis of competition; tax competition; economics; tax rates; tax; competitiveness